Metode Demonstrasi Mata Pelajaran Fiqih Praktik Tayamum - Sulaiman, Husnan; Amelia, Rosa (STAI Al-Musaddadiyah Garut, 2022)
This research is motivated by the researcher's attention to the continuity of the teaching and learning process in the use of teaching methods for the subject of Fiqh, particularly in the practical aspects of the subject. According to the researcher's observations, many students in class VII-8 at MTsN 1 Garut still have a limited understanding of the practice of tayammum. Therefore, the application of practical teaching methods is needed. The objective of this research is to describe the implementation of the demonstration teaching method on the practice of tayammum among students in class VII-8 at Madrasah Tsanawiyah Negeri 1 Garut. The method used in this research is a descriptive qualitative method, which aims to describe or illustrate events in the field. The data collection techniques include observation, interviews, and documentation. The data analysis used in this research involves data reduction, data display, and conclusion drawing. The results of this study indicate that the implementation of the demonstration method in the Fiqh subject on the practice of tayammum for class VII-8 at MTsN 1 Garut can provide a stimulus for students to practice tayammum correctly. Keywords: Demonstration Method, Fiqh Subject, Tayammum Practice